2019
DOI: 10.5205/1981-8963-v13i5a239229p1288-1294-2019
|View full text |Cite
|
Sign up to set email alerts
|

Necessidades das mulheres com câncer de mama no período pré-operatório

Abstract: RESUMO Objetivo: conhecer as necessidades de cuidados no período pré-operatório para a ressecção tumoral na percepção de mulheres com câncer de mama e enfermeiros. Método: trata-se de um estudo qualitativo, descritivo, realizado em uma instituição oncológica, com 18 mulheres com câncer de mama em período pós-operatório e 13 enfermeiros. Utilizou-se para a coleta de dados um roterido de entrevista semiestruturado, composto por três perguntas abertas. Utilizou-se a Análise Temática para a organização e analise d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…This finding agreed with Tuominen et al ( 2020) who concluded that, patients expected to be treated with humanity, which involved receiving support, compassion, and confidence. Also Trescher et al (2019) a qualitative, descriptive study on women with breast cancer was conducted at a Brazilian oncological institution to determine the preoperative care needs for tumour removal in the perception of women with breast cancer and nurses. They stated that providing a humane and compassionate service by nurses, with educational support, healthcare given to women to return to their normal routines, with autonomy and emotional and affective security, decreasing stressors, and promoting the recovery of health is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…This finding agreed with Tuominen et al ( 2020) who concluded that, patients expected to be treated with humanity, which involved receiving support, compassion, and confidence. Also Trescher et al (2019) a qualitative, descriptive study on women with breast cancer was conducted at a Brazilian oncological institution to determine the preoperative care needs for tumour removal in the perception of women with breast cancer and nurses. They stated that providing a humane and compassionate service by nurses, with educational support, healthcare given to women to return to their normal routines, with autonomy and emotional and affective security, decreasing stressors, and promoting the recovery of health is crucial.…”
Section: Discussionmentioning
confidence: 99%